O046 Poor sleep quality is associated with unemployment and lower levels of participation in people living with spinal cord injury. (9th November 2022) - Graco, M; Arora, M; Berlowitz, D; Craig, A; Middleton, J
Abstract: Introduction: Poor sleep is common among people with spinal cord injury (SCI), yet little is known about its impact on employment and participation outcomes. This study aimed to describe the sleep quality of a large sample of Australians with SCI; examine associations between sleep quality and participant characteristics; and explore the relationship between sleep and outcomes. Methods: Cross-sectional Australian survey, including 1579 community-dwelling people with SCI, aged 18 years and over. Sleep quality was assessed with the Pittsburgh Sleep Quality Index (PSQI). Relationships between participant characteristics, sleep and other outcomes were examined with linear and logistic regression. Results: The PSQI was completed by 1172 individuals; 68.4% reported poor sleep (PSQI>5). Subjective sleep quality in people with SCI was poor (mean(SD) PSQI global score=8.5(4.5). Financial hardship and problems with other secondary health conditions were significantly associated with worse sleep quality (p<0.05). Poor sleep quality was strongly associated with lower emotional wellbeing and energy, and greater problems with participation (p<0.001). Individuals engaged in paid work reported better sleep quality than unemployed individuals (mean(SD) PSQI=8.1(4.3) vs 8.7(4.6), p<0.05). Following adjustment for age, pre-injury employment, injury severity and years of education, better sleep quality remained strongly associated with being employed (OR=0.95, 95% CI=0.92-0.98), p=0.003). Conclusions: This study has demonstrated pervasive and impactful relationships between sleep quality and important SCI outcomes. Poor sleep quality was strongly associated with worse emotional wellbeing and vitality, unemployment and lower participation. Determining whether treating sleep problems can improve outcomes for people living with SCI deserves more attention.